DINAMIKA PEMILIHAN KETUA RUKUN TETANGGA (KASUS PEMILIHAN KETUA RT 05 RW 06 KELURAHAN TANJUNG RHU KECAMATAN LIMAPULUH KOTA PEKANBARU) - Ramadhan, Alfian; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The research is based on an election the head of RT 05 RW 06 period from 2015 to 2020 which is held by the election committee but in practice had problems, as the election committe not be neutral, choosing participants voters and the implementation of the election not according to Pekanbaru Mayor Regulation Number 18.a of 2008. The aims of this research to know the head of RW 06 efforts in solve the problems that occured when the head of RT 05 RW 06 election so that in the next elections can be more controlled adn conducive. Method used in this research is descriptive methods with qualitative type. Types of data on this researchis primary and secondary data. The data collected in this research is documentation and interview. The technical data analysis used is descriptive qualitative data analysisThe results showed that holding the head of RT 05 RW 06 election, the period from 2015 to 2020 was not entirely based on the Pekanbaru Mayor Regulation Number 18.a of 2008. It is seen from some of the data obtained from the Urban village, the election committee, as well as the field data collected. The solution to solves the problems in the head of RT 05 RW 06 election is in organizing the head of RT 05 election hereinafter, the election committee must make the Pekanbaru Mayor Regulation Number 18.a of 2008 as a guidance in conducting the head of neighborhood election.Keywords: The Head of Neighborhood Elections, Participants Voters andElection Committe.